Viral Surveillance of Children with Acute Respiratory Infection in Two Main Hospitals in Northern Jordan, Irbid, during Winter of 2016 - Awad, Samah; Khader, Yousef; Mansi, Moa'th; Yusef, Dawood; Alawadin, Salah; Qudah, Walaa; Khasawneh, Ruba (Journal of Pediatric Infectious Diseases, 2020)
Acute lower respiratory infection (ALRI) is a major cause of morbidity and mortality worldwide. Data regarding the etiology of acute respiratory infection (ARI) is scarce in developing countries. The aim of this study was to identify the viral etiology of ARI/ALRI in hospitalized children and factors associated with increased length of stay (LoS) and severe disease presentation in Northern Jordan. This was a prospective viral surveillance study using real-time reverse transcriptase-polymerase chain reaction in children younger than 5 years admitted with ARI to two main hospitals in Northern Jordan during the winter of 2016. Nasopharyngeal swabs were obtained and tested for respiratory syncytial virus (RSV) and other viruses. Demographic and clinical characteristics of RSV-positive patients were compared with those of RSV-negative patients. There were 479 patients hospitalized with ARI. Their mean age (standard deviation) was 10.4 (11.6) months. 53.9% tested positive for at least one virus, with RSV being the most commonly detected virus (34%). Compared with RSV-negative patients, RSV-positive patients were younger, more likely to have chronic lung disease, and more likely to present with cough, rhinorrhea, difficulty in breathing, retraction, flaring, grunting, wheezing, and a higher respiratory rate. Prematurity, presence of a chronic illness, oxygen saturation < 90%, and atelectasis and consolidation on chest X-rays were significantly associated with an increased mean LoS. Patients with a history of prematurity had higher risk of severe disease (odds ratio = 2.6; 95% confidence interval: 1.5, 4.7; p = 0.001). Compared with patients 6 months old and younger, patients aged 6.1 to 12 months were less likely to have severe disease. Human metapneumovirus (HMPV)-positive ALRI was associated with increased odds of severe disease. Viruses are recognized as etiological agent of ARI/ALRI-associated morbidity in developing countries that need more attention and implementation of targeted strategies for prevention and detection. HMPV can be a cause of severe ALRI.
Keywords: acute respiratory infection; children; Jordan; respiratory syncytial virus; RT-PCR